Lesser Known Uses of γ‐Aminobutyric Acid Analogue Medications in Otolaryngology. (18th September 2021) - Miller, Nathaniel; Noller, Michael; Yang, Alex; McCoul, Edward D.; Tolisano, Anthony M.; Riley, Charles A.
Abstract : Objectives/Hypothesis: In otolaryngology, γ‐aminobutyric acid (GABA) analogues have been previously analyzed for their roles in neuropathic pain, chronic cough, tinnitus, and perioperative analgesia. The primary aim of this study is to comprehensively summarize and synthesize the existing evidence for lesser known uses of gabapentin and pregabalin in otolaryngology. Study Design: A scoping review conducted of the available English‐language literature was performed by two authors through April 1, 2021. Methods: The Preferred Reporting Items for Systematic Review and Meta‐Analysis criteria were followed, and a quality assessment of included studies was performed using the Methodological Index for Non‐Randomized Studies. Results: Ten studies met inclusion criteria. Three studies found that gabapentin may reduce gastrostomy tube usage and improve swallowing function in head and neck cancer patients undergoing radiation therapy (RT). Three studies suggested that gabapentin may help reduce opiate use when used as a primary analgesic in patients with radiation‐induced mucositis. One study demonstrated that pregabalin‐reduced trismus severity in patients with radiotherapy‐induced trismus. One study demonstrated gabapentin may be useful in patients with phonasthenia. Two studies demonstrated that GABA analogues may be a useful adjunct in patients with globus pharyngeus in the context of likely laryngeal sensory neuropathy. Conclusions: The most promising potential uses for GABA analogues identified in this review are for improving swallowing, trismus, and narcotic overuse after RT. The benefit of GABA analogues for improving nonorganic voice disorders is also promising while the benefit for globus pharyngeus when possibly related to laryngeal sensory neuropathy is inconclusive. Laryngoscope, 132:954–964, 2022